Student and Teacher Perceptions of Online Student Engagement in an Online Middle School - Nathaniel Louwrens; Maggie Hartnett (Flexible Learning Association of New Zealand, 2015)
While our understanding of student engagement in the compulsory schooling sector is well developed in face-to-face contexts, the same cannot be said for online and distance learning environments. Indeed, most of what is currently known about online engagement has come from research with older students in tertiary education contexts. This study directly addresses this gap in the research by exploring student engagement in an online, middle school in a New Zealand distance education context. By considering three key dimensions of student engagement-namely, behavioural engagement, cognitive engagement, and emotional engagement-this in-depth investigation explores what engages middle school students when they learn online. Data collection techniques comprised student and teacher interviews, online asynchronous discussion transcripts, and statistical data from the learning management system (LMS). Results found that students in this study tended to engage behaviourally (i.e., do what was expected of them) with all required activities. Cognitive engagement (i.e., students' personal investment in their own learning) was evident in the giving and receiving of feedback as well as the interest and relevance certain activities generated for learners. Emotional engagement was elicited through the design and facilitation of the activities, and through the ongoing development of a learning community in which students felt safe to contribute.